Preliminary evaluation of near infrared spectroscopy as a method to detect plasma leakage in children with dengue hemorrhagic fever - Soller, Babs (BMC Infect Dis, 2014)
BACKGROUND: Dengue viral infections are prevalent in the tropical and sub-tropical regions of the world, resulting in substantial morbidity and mortality. Clinical manifestations range from a self-limited fever to a potential life-threatening plasma leakage syndrome (dengue hemorrhagic fever). The objective of this study was to assess the utility of near infrared spectroscopy (NIRS) measurements of muscle oxygen saturation (SmO(2)) as a possible continuous measure to detect plasma leakage in children with dengue. METHODS: Children ages 6 months to 15 years of age admitted with suspected dengue were enrolled from the dengue ward at Queen Sirikit National Institute for Child Health. Children were monitored daily until discharge. NIRS data were collected continuously using a prototype CareGuide Oximeter 1100 with sensors placed on the deltoid or thigh. Daily ultrasound of the chest and a right lateral decubitus chest x-ray the day after defervescence were performed to detect and quantitate plasma leakage in the pleural cavity. RESULTS: NIRS data were obtained from 19 children with laboratory-confirmed dengue. Average minimum SmO(2) decreased for all subjects prior to defervescence. Average minimum SmO(2) subsequently increased in children with no ultrasound evidence of pleural effusion but remained low in children with pleural effusion following defervescence. Average minimum SmO(2) was inversely correlated with pleural space fluid volume. ROC analysis revealed a cut-off value for SmO(2) which yielded high specificity and sensitivity. CONCLUSIONS: SmO(2) measured using NIRS may be a useful guide for real-time and non-invasive identification of plasma leakage in children with dengue. Further investigation of the utility of NIRS measurements for prediction and management of severe dengue syndromes is warranted.